2009
DOI: 10.1007/s10877-009-9181-0
|View full text |Cite
|
Sign up to set email alerts
|

Bi-spectral index guided closed-loop anaesthesia delivery system (CLADS™) in pheochromocytoma

Abstract: CLADS performed well in patients undergoing pheochromocytoma surgeries which represent one of the few clinically extreme situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…37 The most frequently used control signal has been the Bispectral Index (BIS). 7-9,11,13,14,17,18,21-23,38-40 Other control signals have included a wavelet-based index, 12 entropy measures, 16 an auditory evoked potential index 15 and the spectrogram median frequency. 24-26 These systems have been constructed with standard and nonstandard control paradigms 15,16,23,24,40 and used principally to control unconsciousness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 The most frequently used control signal has been the Bispectral Index (BIS). 7-9,11,13,14,17,18,21-23,38-40 Other control signals have included a wavelet-based index, 12 entropy measures, 16 an auditory evoked potential index 15 and the spectrogram median frequency. 24-26 These systems have been constructed with standard and nonstandard control paradigms 15,16,23,24,40 and used principally to control unconsciousness.…”
Section: Discussionmentioning
confidence: 99%
“…24 In contrast, several of the studies that used BIS as the control signal defined successful control as a BIS value between 40 to 60, and reported BIS time courses averaged across subjects. 7-9,11,13,14,17,18,21-23,38-40 Control using BIS as a control signal is achieved with a 20- to 30-s delay required to compute the BIS updates. 41 Those CLAD systems that have been developed to study burst suppression have also only shown results for time courses averaged across subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a few clinical studies of closed-loop control have been done and have shown to outperform manual administration of drugs [33,36,39,58]. However, these controllers were designed based on subjective clinical experience rather than optimization of the process.…”
Section: Closed-loop Applicationmentioning
confidence: 99%
“…Recently, they compared the accuracy of their system with manual control during cardiac surgery and concluded that automated control was safe, efficient and performed better than manual control [61 ]. Additionally, they proved the feasibility of their system during pheochromocytoma surgery [62].…”
Section: Closing the Loopsmentioning
confidence: 99%